Pilgrimage - Leibovitz, Annie, 1949- (Random House, 2011)
"Pilgrimage took Annie Leibovitz to places that she could explore with no agenda. The first place was Emily Dickinson's house in Amherst, Massachusetts. A few months later, she went with her three young children to Niagara Falls.She added the houses of Virginia Woolf and Charles Darwin in the English countryside and Sigmund Freud's final home, in London, but most of the places on the lists were American. Leibovitz went to Concord to photograph the site of Thoreau's cabin at Walden Pond. Once she got there, she was drawn into the wider world of the Concord writers. Ralph Waldo Emerson's home and Orchard House, where Louisa May Alcott and her family lived and worked, became subjects. The Massachusetts studio of the Beaux Arts sculptor Daniel Chester French, who made the seated statue in the Lincoln Memorial, became the touchstone for trips to Gettysburg and to the archives where the glass negatives of Lincoln's portraits have been saved. Lincoln's portraitists--principally Alexander Gardner and the photographers in Mathew Brady's studio--were also the men whose work at the Gettysburg battlefield established the foundation for war photography. At almost exactly the same time, in a remote, primitive studio on the Isle of Wight, Julia Margaret Cameron was developing her own ultimately influential style of portraiture. Leibovitz made two trips to the Isle of Wight and, in an homage to the other photographer on her list, Ansel Adams, she explored the trails above the Yosemite Valley, where Adams worked for fifty years. The final list includes Georgia O'Keeffe, Eleanor Roosevelt, Elvis Presley and Annie Oakley, among others. Figurative imagery gives way to the abstractions of Old Faithful and Robert Smithson's Spiral Jetty.